Tanggung Jawab Notaris Dalam Menjaga Keamanan Digitalisasi Akta - Theixar, Regina Natalie; Dharmawan, Ni Ketut Supasti (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 6 No 01 (2021), 2021)
The purpose of this research is to examine notary’s roles and responsibilities regarding data security of the parties. This study uses normative legal research methods. The results of this study indicate that the misuse of digital signatures can be avoided by taking preventive measures, such as increasing the security of computer device securities in accordance with the UN Congress Resolution policy standards as outlined in the Information and Electronic Transaction Law and Government Regulations on the Implementation of Electronic Systems and Transactions, one of which is the use of digital signature based on digital certificate. However, if the notary fails to maintain the security and data confidentiality of the parties in the deed that they make and keep, it can be related to neglecting to carry out the Notary's obligations in article 16 letter (f), to keep everything about the Deed made by the Notary confidential. Administrative sanctions for notary negligence include written warnings, temporary dismissal, honorific dismissal, or dishonorable dismissal. If the Notary is proven to have deliberately manipulated or caused the loss or damage of the deed so that it fulfills the elements of an illegal act based on Article 1365 of the Civil Code, civil and criminal sanctions may be imposed. Tujuan penelitian ini yaitu untuk mengkaji peran dan tanggung jawab notaris berkaitan dengan keamanan data para pihak. Studi ini menggunakan metode penelitian hukum normatif. Hasil penelitian ini mengunjukkan bahwa penyalahgunaan tanda tangan digital dapat dihindari dengan tindakan preventif yakni meningkatkan keamanan sekuritas perangkat komputer sesuai dengan standar kebijakan Resolusi Kongres PBB yang dituangkan dalam Undang-Undang Informasi dan Transaksi Elektronik serta Peraturan Pemerintah Penyelenggaraan Sistem dan Transaksi Elektronik, salah satunya dengan penggunaan digital signature berdasarkan digital certificate. Namun apabila notaris gagal menjaga keamanan dan kerahasiaan data para pihak dalam akta yang dibuat dan disimpannya, dapat dikaitkan dengan lalai menjalankan kewajiban Notaris dalam pasal 16 huruf (f) yakni merahasiakan segala sesuatu mengenai Akta yang dibuat Notaris. Sanksi administratif atas kelalaian notaris berupa peringatan tertulis, pemberhentian sementara, pemberhentian dengan hormat, atau pemberhentian dengan tidak hormat. Apabila Notaris terbukti dengan sengaja memanipulasi atau menyebabkan hilang maupun rusaknya akta sehingga memenuhi unsur perbuatan melawan hukum berdasarkan Pasal 1365 Kitab Undang-Undang Hukum Perdata, dapat dikenakan sanksi perdata dan pidana.